SARS-COV-2 vaccine acceptance in patients with rheumatic diseases: a cross-sectional study - Tina Ko; Claire Dendle; Ian Woolley; Eric Morand; Anna Antony (Taylor & Francis Group, 2021)
Objectives To evaluate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine acceptance among patients with rheumatic diseases (RMD). Methods All rheumatology patients attending a large suburban health network were invited to participate in an anonymized online survey. The primary outcome of interest was SARS-COV-2 vaccine acceptance. Results The mean (SD) age of respondents (n = 641) was 52.7 (15.1) years and 74.4% (n = 474) were female. Sixty-five percent were willing to have a SARS-COV-2 vaccine, while 34.4% were vaccine-hesitant (unwilling or undecided). On multivariate analysis, vaccine acceptance was associated with smoking (OR: 2.25 [95% CI: 1.22-4.15; p = .009]), history of malignancy (OR: 2.51 [95% CI: 1.19-5.26; p = .015]), influenza or pneumococcal vaccination in the preceding year (OR: 2.69 [95% CI: 1.78-4.05; p < .001]) and number of COVID-Safe measures practiced (OR: 1.54 [95% CI: 1.05-2.26; p = .027]). Vaccine acceptance correlated with positive beliefs regarding vaccine efficacy (r = 0.40; p < .001) and safety (r = 0.36; p < .001). Vaccine acceptance correlated negatively with concerns regarding side-effects (r = −0.30; p < .001) and vaccine-associated RMD flare (r = −0.21; p < .001). In vaccine-hesitant respondents, 39.2% were more likely to accept vaccination if given a choice of which vaccine they receive and 54.5% if their rheumatologist recommended it. Twenty-seven percent of patients on immunomodulators were willing to withhold medications while 42.1% were willing if advised by their rheumatologist. Conclusion SARS-COV-2 vaccine hesitancy is prevalent amongst RMD patients and associated with concerns regarding vaccine safety, efficacy, side effects and RMD flare. Clinician recommendation, vaccine choice and communications targeting patient concerns could facilitate vaccine acceptance. Significance and Innovations Vaccine hesitancy is prevalent in RMD patients Vaccine acceptance is associated with beliefs regarding vaccine safety and efficacy and concerns regarding RMD flare and vaccine-associated side effects Vaccine choice and clinician recommendation have the potential to improve vaccine acceptance in patients who are hesitant